A Study on the Internal Erosion of Gap-Graded Soils - Malihe Nazari; Ali Maroof; Ali Akhtarpour; Jafar Bolouri (آب و توسعه پایدار)
Internal erosion is a common reason for dam failure, which is caused by soil subsidence and the formation of sinkholes. This phenomenon typically occurs in internally unstable soils. The dam is located in Neyshabour City and is built on a deep alluvial foundation with gap-graded and concave gradation soils. This study aims to investigate the potential for soil suffusion and the impact of compaction and surcharge on internal erosion. Initially, Data was collected after the dam impounding, index tests were conducted on soil samples. Subsequently, three methods were used to assess the probability of suffusion based on the particle size distribution and experimental criteria. Two methods indicated soil was internally unstable, while one method indicated stability. To study the influence of compaction. Soil samples were tested at different densities under four water head conditions. The results indicated that the soil has the potential for suffusion and is internally unstable. Furthermore, the study found that compaction reduced soil erosion, with the amount of washed fine particles decreasing from 4.5% at 70% relative density to 0.37% at 85% density. Moreover, increasing compaction from 70% to 85% resulted in a deformation decrease from 13.3% to 3.33%.